1992
DOI: 10.1055/s-2008-1071353
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of GABA Metabolism in Pyridoxine-Dependent Seizures

Abstract: In an infant with typical pyridoxine-dependent seizures, CSF GABA level, was determined before treatment with pyridoxine. Before onset of treatment, level of GABA in CSF was highly lowered (16 pmol/ml), pyridoxine level in serum was within normal range. Immediately after application of 80 mg pyridoxine fits stopped and the EEG was without seizure activity. The data substantiate previous findings in brain tissue from a patient with pyridoxine-dependent seizures. They are proof of a disturbed GABA metabolism in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…conversion to GABA is impaired [Lott et al, 1978;Kurlemann et al, 1992;Baumeister et al, 1994]. Similar demonstrations of low GABA concentrations in the brain and cerebrospinal fluid (CSF) during states of pyridoxine-deficiency [Coursin, 1954] as well as during states of pyridoxyl phosphate inhibition [Gospe, 1998], e.g.…”
Section: Pyridoxine-dependent Seizures-the Disordermentioning
confidence: 88%
“…conversion to GABA is impaired [Lott et al, 1978;Kurlemann et al, 1992;Baumeister et al, 1994]. Similar demonstrations of low GABA concentrations in the brain and cerebrospinal fluid (CSF) during states of pyridoxine-deficiency [Coursin, 1954] as well as during states of pyridoxyl phosphate inhibition [Gospe, 1998], e.g.…”
Section: Pyridoxine-dependent Seizures-the Disordermentioning
confidence: 88%
“…These disorders include pyridoxine-dependent epilepsies, GABA-transaminase deficiency and succinic-semialdehyde-dehydrogenase deficiency (Battaglioli et al, 2000;Gibson et al, 1998;MedinaKauwe et al, 1999). Subjects with pyridoxine-dependent epilepsies have been observed to have extremely low CSF GABA levels, elevated glutamate, and low levels of brain GABA (Kurlemann et al, 1992;Kure et al, 1998;Battaglioli et al, 2000). Recent reports have suggested that similar changes in CSF GABA occur in children with infantile spasms (Ohtsuka et al, 2000).…”
Section: Part Ii: Mrs Studies Of the Role Of Gaba In Epilepsymentioning
confidence: 97%
“…However, recent evidence has thrown doubt on this theory and molecular diagnosis is still not available (Battaglioli et al 2000). Thus, the observation of recurrent seizures after pyridoxine withdrawal has been the only available way of establishing a definitive diagnosis of pyridoxine dependency (Kurlemann et al 1992, Baumeister et al 1994, Gospe 1998. A non-intentional trial was carried out in this case when the vitamin complex containing pyridoxine, given as supplementation, was withdrawn at 70 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…It has been thought that a defect in glutamate decarboxylase apoenzyme binding of its cofactor pyridoxal phosphate could be the underlying molecular defect in pyridoxine-dependent seizures (Lott et al 1978, Kurlemann et al 1992, Baumeister et al 1994, Gospe et al 1994, Gospe 1998). However, recent evidence has thrown doubt on this theory and molecular diagnosis is still not available (Battaglioli et al 2000).…”
Section: Discussionmentioning
confidence: 99%